Tuina for children with cerebral palsy: A protocol for a systematic review. Issue 4 (January 2018) - Guo, Tainpin; Zhu, Bowen; Zhang, Xinghe; Xu, Na; Wang, Hourong; Tai, Xiantao
Abstract: Background: Cerebral palsy (CP) describes a group of permanent disorders of movement and posture causing activity limitations, leading the most common movement disorder to children. On recovery of various aspects of CP, massotherapy has a good effect in a great many of Chinese clinical trials. Therefore, we plan to conduct a protocol of systematic review aimed at systematically reviewing all the clinical evidence on the effectiveness of massotherapy for treating CP in children. Methods: The following electronic databases will be searched from inception to October 1, 2017: Cochrane Library, Web of Science, EBASE, Springer, World Health Organization International Clinical Trials Registry Platform, China National Knowledge Infrastructure, Wan-fang database, Chinese Biomedical Literature Database, Chinese Scientific Journal Database, and other sources. All published English and Chinese articles randomized controlled trials (RTCs) will be included. All types of CP of children in the trials will be included in this study and these individuals will be involved as coresearchers to evaluate the efficacy of massothreapy. RevMan V.5.3.5 software will be implemented for the assessment of bias risk, data synthesis, subgroup analysis, and meta-analyses if inclusion conditions are met. Continuous outcomes will be presented as mean difference (MD) or standard mean difference (SMD), while dichotomous data will be expressed as a relative risk. Results: A high-quality synthesis of current evidence of massothreapy for children with CP will be provided from several aspects, including motor function improvement, intellectual development, improvement of self-care ability, and daily living. Conclusion: This protocol will present the evidence of whether Tuina threapy is an effective intervention for children with CP. Ethics and dissemination: There is no requirement of ethical approval and it will be in print or disseminated by electronic copies. PROSPERO registration number: CRD42017080342.